MEMBENTUK KEMAMPUAN PSIKOLOGIKAL DASAR CALON AKTOR DENGAN METODE LATIHAN BERTUTUR - Niaga, Ipong (Institut Seni Indonesia Padang Panjang, 2014)
Acting andsome of its problems, especiallyhow to prepare agood actor,requirescontinuous search of training methods to find appropriate solutions.Stanislavskiâs methoddistinguishes twokinds of factorsthatneed to be trainedinacting, namey the external factor and internal factor. The external factorincludes body and voice, while the internal factor refers to psychological aspects.Each factor should be absolutely combined in presenting characters on stage.With its own level of difficulty, actors are required to train both factors in orderto achieve complex skills. This study will discuss one the two factors above, thatis, the internal factor that calls for preparation of basic psychological skills suchas concentration, observation, and emotion. Through the method of speech, thisstudy is meant as an experiment in order to find a right and measurable methodin the process of preparing the actor for the internal factor.